GENESIS AND PROPERTIES OF PEAT AT TOBA HIGHLAND AREA OF NORTH SUMATRA - Bambang Hendro Prasetyo; Nata Suharta (Indonesian Journal of Agricultural Science, 2011)
In Indonesia, peat soil in the highland area is only found in the plateau of Toba Highland, North Sumatra, and its morphologi-cal, physical, and chemical properties have been studied. Four profiles of peat soil were made in the field and eighteen samples were taken and analyzed in laboratory. Most of the properties of highland peat were similar with lowland peat. The differences were in their Al saturation, P retention, and andic soil properties. High Al saturation was resulted from weathering of primary minerals under the acid condition. Andic soil properties were caused by amorphous materials resulted from weathering of volcanic materials in the peat, and P retention was related with the presence of amorphous materials. Phosphate retention of the highland peat was classified high (>60%) and positively correlated with amorphous materials. The presence of amor-phous materials was confirmed by ammonium oxalate extract-able Alo+½Feo. The presence of andic soil properties in the highland peat created problem in their classification. To provide a place for andic soil properties that influence the P retention in the highland peat soil, the soil classification of peat soil should be modified by adding andic modifier at subgroup level.